1995
DOI: 10.1128/mcb.15.10.5434
|View full text |Cite
|
Sign up to set email alerts
|

Meis1, a PBX1-Related Homeobox Gene Involved in Myeloid Leukemia in BXH-2 Mice

Abstract: Leukemia results from the accumulation of multiple genetic alterations that disrupt the control mechanisms of normal growth and differentiation. The use of inbred mouse strains that develop leukemia has greatly facilitated the identification of genes that contribute to the neoplastic transformation of hematopoietic cells. BXH-2 mice develop myeloid leukemia as a result of the expression of an ecotropic murine leukemia virus that acts as an insertional mutagen to alter the expression of cellular proto-oncogenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
278
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 305 publications
(281 citation statements)
references
References 56 publications
3
278
0
Order By: Relevance
“…Some murine HOX genes have been described to be able of transforming murine cells both in vivo and in vitro (Maulbecker and Gruss 1993). In humans, some divergent homeobox containing genes are involved in chromosomal translocations or their expression associated with di erent leukemias (Dedera et al, 1993;Deguchi and Kehre 1993;Hatano et al, 1991;Moskow et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some murine HOX genes have been described to be able of transforming murine cells both in vivo and in vitro (Maulbecker and Gruss 1993). In humans, some divergent homeobox containing genes are involved in chromosomal translocations or their expression associated with di erent leukemias (Dedera et al, 1993;Deguchi and Kehre 1993;Hatano et al, 1991;Moskow et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…The coordinate expression of HOX genes as described in teratocarcinoma (Mavilio 1993), activated T lymphocytes (CareÁ et al, 1994) and progenitor hematopoietic cells (Giampaolo et al, 1994;Sauvageau et al, 1994) appears to be lost in neoplasias of di erent origin (CareÁ et al, 1996;Cillo et al, 1992). The oncogenic potential of several murine Hox genes has been demonstrated by in vitro and in vivo transformation assays (Maulbecker and Gruss, 1993), while divergent human and murine homeobox containing genes such as Pbx1, tcl-3, HB24 and meisl are involved in speci®c chromosomal translocations (Dedera et al, 1993;Hatano et al, 1991) or are associated with di erent leukemias (Deguchi et al, 1993;Moskow et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The proto-oncogene Meis1 was first identified, together with Hoxa7 and Hoxa9, as a common viral integration site in myeloid leukemic cells of BXH-2 mice (Moskow et al, 1995). We and others have subsequently demonstrated that overexpression of Meis1 collaborates with multiple native and NUP98-HOX fusion genes to accelerate the onset of AML in the murine BMT models (Kroon et al, 1998Thorsteinsdottir et al, 2001;Pineault et al, 2003Pineault et al, , 2004Fischbach et al, 2005).…”
Section: Meis1 and Flt3 In Hox-mediated Leukemiamentioning
confidence: 94%
“…Mammalian Meis1 (myeloid ecotropic insertion site 1) was identified initially as a common site of viral integration in mouse myeloid leukemia cells (21), and the related Meis2 and Meis3 genes were identified by sequence similarity (22,23). Meis1 plays a key role in the progression of AML and MLL leukemia, and fusion proteins generated by chromosomal rearrangements in MLL can induce increased expression of Meis1 (24-26).…”
mentioning
confidence: 99%